Mailbox 20 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
MailboxHaven t you written to Spore yet? It s always a quandary, isn t it? You think we may not publish it? You know that we get more letters than we can publish, even if we read and appreciate them all. We just do not have enough space.That is...